Soft Palate Reconstruction Using Bilateral Palatal Mucomuscular Flap and Pharyngeal Flap after Resection of Squamous Cell Carcinoma - Jun Sik Kim; Hyeon Jong Jo; Nam Gyun Kim; Kyung Suk Lee (Archives of Plastic Surgery, 2012)
Squamous cell carcinoma infrequently occurs at the soft palate. Although various methods can be used for reconstruction of soft palate defects that occur after resecting squamous cell carcinoma, it is difficult to obtain satisfactory results from the perspective of the functional restoration of the soft palate. A combination of bilateral palatal mucomuscular flap for the oral side and superiorly based posterior pharyngeal flap for the nasal side were performed on two patients who were diagnosed with squamous cell carcinoma of the soft palate in order to reconstruct the soft palate defects after surgical resection. After surgery, the patients were followed-up for a mean period of 11 months. The flaps were well maintained in both patients. The donor site defects were epithelialized and completely recovered. Additionally, no recurrence of the primary sites was shown. Slight hyponasality was observed in the voice assessments that were conducted 6 months after surgery. No food regurgitation or aspiration was observed in the swallowing tests. We used a combination of bilateral palatal mucomuscular flap and superiorly based posterior pharyngeal flap to reconstruct the soft palate defects that occurred after resecting the squamous cell carcinomas. We reduced the donor site complications and achieved functionally satisfactory outcomes.